PENERAPAN ALGORITMA ANT SYSTEM DALAM MENEMUKAN JALUR OPTIMAL PADA TRAVELING SALESMAN PROBLEM (TSP) DENGAN KEKANGAN KONDISI JALAN - , Andhi Akhmad Ismail, ST., Ir. Samiadji Herdjunanto, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The completion of Traveling Salesman Problem (TSP) is to find the shortest path to visit all of the cities. With the shortest path, it is expected that the travel time will also be shorter. In fact, when a salesman visits all of the cites in his list, he will find obstacles such as poor road conditions, congestion, damaged roads, or other constraints. Therefore, although the shortest path has been established, if there is an obstacle the travel time to all cities will be longer.